MOTIVASI NEGARA DEWAN TELUK (ARAB SAUDI, UEA DAN BAHRAIN) MENARIK DUTA BESARNYA DI QATAR PADA TAHUN 2014 - Sijekto "; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research analyzes reasons the State Council of the Gulf (Saudi Arabia, United Arab Emirates and Bahrain) withdraw its ambassador in Qatar In the Year 2014, the State Council of the Gulf of Interest ambassador in Qatar in 2014 In Qatar caused because the support of the Muslim Brotherhood in Egypt. Muslim Brotherhood in the Gulf region as a terrorist organization that can Endangers security and stability in the Persian Gulf region.This research used qualitative methods and library research. The author uses the theory of Hegemony from Antonio Granchi using Realism perspective with analysis of nation-state level. References obtained from books, journals, official publications, articles, news, and internet.To answer this study, the State Council of the Gulf (Saudi Arabia, United Arab Emirates and Bahrain) recalled its ambassador in Qatar in 2014 to protest the State Council of the Gulf because Qatar is not committed to the treaty Gulf coopertion Countil (GCC) in the Treaty that any State or Individuals must not support any organization that could be a threat. Qatar It supports the Muslim Brotherhood. Muslim Brotherhood in the Gulf Region as a terrorist organization that can lead to security threats and stability in the Gulf region.Keywords: State Council of the Gulf (Saudi Arabia, EUA and Bahrain), Traety Of Coopertion, Ihwanul Muslimin